Discourses of Digitalisation and the Positioning of Workers in Primary Care: A Norwegian Case Study - Nerland, Monika; Hasu, Mervi; Grisot, Miria (Social inclusion, 2023)
Primary health services are subjected to intensified digitalisation to transform care provision. Various smart and assistive technologies are introduced to support the growing elderly population and enhance the opportunities for independent living among patients in need of continuous care. Research has shown how such digitalisation processes evolve at the intersection of different and often competing discourses, oriented towards service efficiency, cost containment, technological innovation, client‐centred care, and digital competence development. Often, increased technology use is presented as a solution to pressing problems. However, how discourses are negotiated in work contexts and their mechanisms of social inclusion/exclusion in evolving work practices have received less attention. This article examines how care workers in the primary health sector are discursively positioned when care technologies are introduced in the services. We employ a perspective on discourses and subject positions in analysing strategic documents and interviews with care workers in a large Norwegian city. We show how managerial discourses that focus narrowly on the implementation and mastery of single technologies provide limited spaces for workers to exert influence on their work situations, while discourses that emphasise professional knowledge or broader technological and organisational aspects provide a variety of resources for workers’ agency. The way care workers adopt and negotiate subject positions varies based on their tasks and responsibilities in the organisation. We discuss the need to move beyond “solutionism” in efforts to digitalise care work in order to provide inclusive spaces supporting the contributions of various worker groups.